Human urotensin-II is a potent spasmogen of primate airway smooth muscle - Hay, Douglas W P (2000)
The contractile profile of human urotensin-II (hU-II) was examined in primate airway and pulmonary vascular tissues. hU-II contracted tissues from different airway regions with similar potencies (pD(2)s from 8.6 to 9.2). However, there were regional differences in the efficacy of hU-II, with a progressive increase in the maximum contraction from trachea to smaller airway regions (from 9 to 41% of the contraction to 10 μM carbachol). hU-II potently contracted pulmonary artery tissues from different regions with similar potencies and efficacies: pD(2)s=8.7 to 9.3 and maximal contractions=79 to 86% of 60 mM KCl. hU-II potently contracted pulmonary vein preparations taken proximal to the atria, but had no effect in tissues from distal to the atria. This is the first report describing the contractile activity of hU-II in airways and suggests that the potential pathophysiological role of this peptide in lung diseases warrants investigation.